Conducting Helical Structures from Celery Decorated with a Metallic Conjugated Polymer Give Resonances in the Terahertz Range. (21st February 2018) - Elfwing, Anders; Ponseca, Carlito S.; Ouyang, Liangqi; Urbanowicz, Andrzej; Krotkus, Aru–nas; Tu, Deyu; Forchheimer, Robert; Inganäs, Olle
Abstract: A method to decorate cellulose‐based helices retrieved from the plant celery with a conductive polymer is proposed. Using a layer‐by‐layer method, the decoration of the polyanionic conducting polymer poly(4‐(2, 3‐dihydrothieno [3, 4‐b]‐[1, 4]dioxin‐2‐yl‐methoxy)‐1‐butanesulfonic acid (PEDOT‐S) is enhanced after coating the negatively charged cellulose helix with a polycationic polyethyleneimine. Microscopy techniques and two‐point probe are used to image the structure and measure the conductivity of the helix. Analysis of the optical and electrical properties of the coated helix in the terahertz (THz) frequency range shows a resonance close to 1 THz and a broad shoulder that extends to 3.5 THz, consistent with electromagnetic models. Moreover, as helical antennas, it is shown that both axial and normal modes are present, which are correlated to the orientation and antenna electrical lengths of the coated helices. This work opens the possibility of designing tunable terahertz antennas through simple control of their dimensions and orientation. Abstract : Using a biotemplating procedure, a conducting coil is produced from a helical bundle of celery fibers coated with a conductive polymer. The coated structure shows resonance in the terahertz region.